ANALISIS RESIDU PESTISIDA PADA BUAH TOMAT DI SULAWESI SELATAN - Januati Januati (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2020)
Pesticide residues in agricultural products can cause health problems. This study aims to analyze the level of use of chemical pesticides by farmers on tomatoes and analyze how much the residual content of pesticides contained in tomatoes produced in Maros, Gowa and Enrekang districts. This type of observational survey research with a descriptive approach. Sampling using a purposive sampling method. Tomato samples were taken randomly from farmers and market traders who sold tomatoes and were busy with buyers from three Kaba Regencies namely Enrekang, Maros and Gowa. Inspection of the sample of the extraction stage was carried out at the UPTD BPTPH Sul-Cell Pesticide Testing Laboratory and the Analysis phase was carried out at the Jakarta Sunday Market Product Quality Testing Center using the GC Agilent 7890A tool. The results of the analysis of the content of pesticide residual chlorpyrifos levels in the MRPT sample (Maros Petani, Camba District) were detected 0.459 mg / kg, the number was still below BMR but it was close to the required 0.5 mg / kg threshold, while the chlorpiriphos content in the MRPS (the Maros Market) was detected 0.129 mg / kg and MLPS (Malino Market) was detected 0.023 mg / kg, Chlorpirifos levels in MLPT (Malino Petani, High Moncong District), ENPT (Enrekang Petani, Baroko District) and ENPS (Enrekang Pasar) were not detected in the detection limit of the instrument is 0,000 (3 digits behind the comma), propenophos levels in the MRPT sample (Maros Petani, Camba Disguisance) detected 0.410 mg / kg, MRPS (Maros Market) detected 0.016 mg / kg, MLPT (Malino Petani, High District Muzzle) detected 0.011 mg / kg, ENPT (Enrekang Petani, Baroko District) detected 0.012 mg / kg, ENPS (Enrekang Pasar) detected 0.049 mg / kg and only in MLPS (Malino Market) which were not detected but did not rule out the possibility of being detected the detection of tools with a higher level of accuracy, besides that it does not cover it is also possible to be detected in other active ingredients besides chlorophyllos, because farmers use a variety of pesticides other than those made from chlorpiriphos and propenophos. Related institutions to increase counseling to farmers and sellers of tomatoes in the market.